Factors Associated with Food Insecurity among the Urban B40 Group in Kuching, Sarawak, During the Covid-19 Pandemic - Yeo, Zi Sheng; Cheah, Whye Lian (Faculty of Public Health, Mahidol University, Thailand, 2024)
Movement restrictions were one of many measures used to reduce the spread of the Covid-19 disease in Malaysia. The movement restrictions in Malaysia included suspending international travel, prohibiting gatherings, closure of non-essential business, and limiting travel distances. These restrictions negatively affected the economy, especially those already in poverty. The poor now have less capacity to attain safe and sufficient nutritious food to meet their dietary requirements for an active and healthy lifestyle. In Malaysia, those in poverty are grouped into the B40 income group, representing the bottom 40 per cent of income makers in Malaysia. This study determined the factors associated with food insecurity among the urban B40 group in Kuching, Sarawak, during the Covid-19 pandemic. This cross-sectional quantitative study collected data face-to-face using structured questionnaires from 302 urban B40 households in Kuching, Sarawak.